Synthesis of (Z)-Cinnamate Esters by Nickel-Catalyzed Stereoinvertive Deoxygenation of trans-3-Arylglycidates - Akkarasamiyo, Sunisa; Chitsomkhuan, Saranya; Buakaew, Supawadee; Samec, Joseph S. M.; Chuawong, Pitak; Kuntiyong, Punlop (Synlett, 2022)
We report a stereoinvertive deoxygenation of trans-3-arylglycidates as an alternative route to access thermodynamically less stable (Z)-cinnamate esters by using nickel triflate and triphenylphosphine. Broad functional-group tolerance was observed, with trans-3-arylglycidates containing methyl, methoxy, halo, or nitro groups affording the corresponding (Z)-cinnamate esters in high yields and with moderate to high E/Z ratios.
Keywords: deoxygenation; epoxides; cinnamate esters; nickel catalysis